Lean production system knowledge improvement by implementing lean production system simulation game at WSA Engineering Sdn Bhd - Hajar, Abdullah (2012)
This final year project is about Lean Production System (LPS) Simulation Game that had been applied at WSA Engineering Sdn Bhd. LPS simulation game is a tool for education and training purpose for the employees at WSA Engineering Sdn Bhd in improving their knowledge in Lean Production System. As LPS will be widely used in Malaysia, so there is need a tool in smoothing the LPS implementation. Before implement this LPS, the industry need to develop the LPS skills among the employees. So this step are taken by WSA Engineering Sdn Bhd by implementing this LPS Simulation Game in their company. Therefore, objectives of this project is to train all of the employees to achieve standard in doing work, follow the standard operation procedure (SOP). Besides, to acquire the skills to build optimal quality in the manufacturing processes, secure required volume and pursue cost reduction. The problem statement of this project is LPS or Kaizen team at WSA Engineering Sdn Bhd had difficulties to implement and develop the LPS knowledge among the employees. For the previous condition, the Production team had been run the training but it is the theory only not expose with the simulation game. Through teory, the the employees not really understand and cannot relate with the real condition at the work environment. Then, WSA LPS team had been setup one simulation games which are Kanban Simulation Game. After running the training, the achievement of the employees is increase which are the percentage of rejection is decrease. So, for the current condition the training had been run but with the difference strategies where the idea of this project is come out, which is lump sum the three simulation game which are Kanban Simulation Game, Majaico Tower Simulation Game and Restaurant Game to become LPS Simulation Game. In order to reinforce the learning process and measure the effectiveness of this game in teaching items of LPS, surveys to test pre-game knowledge and post-game knowledge are administered before and after the game to the WSA employees. So, from this the level of LPS knowledge between pre-training and post-training can be evaluated. Besides, during the simulation game running, each group will be evaluated based on the parameters measured through them. That parameters are shipped quantity, cost per piece, profit and customer satisfaction and through that, they will realized about the relationship between shipped quantity, company profit and customer satisfaction, and for the other side is between processing cost and cost per piece. Through the finding of this project, this simulation game enhanced the learning and understanding of basic concepts of lean because of during the simulation game all of the participants have been exposed with all of the LPS items.